Prototype of Greenhouse Effect for Improving Problem-Solving Skills in Science, Technology, Engineering, and Mathematics (STEM)-Education for Sustainable Development (ESD): Literature Review, Bibliometric, and Experiment (Indonesian Journal of Science and Technology, 2024)
This research aims to improve problem-solving abilities regarding the greenhouse effect using project-based learning methods supported by Science, Technology, Engineering, and Mathematics (STEM)-Education for Sustainable Development (ESD)-based teaching materials. The study was conducted in multiple phases: (i) utilizing a pretest to gauge students' prior knowledge, (ii) employing the project-based learning approach to teach the greenhouse effect, and (iii) assessing students' final knowledge (with a posttest). The research was completed with the observation of temperature variations in a greenhouse prototype. Students monitored and recorded temperature changes over time. Students' problem-solving abilities increased significantly after being treated using project learning assisted by STEM-ESD teaching materials, imparting more information through the media by stimulating students' curiosity and interest in science subjects.
Keywords: ESD; Greenhouse effect; Problem-solving; STEM